Itaconic Acid Increases the Efficacy of Tobramycin against Pseudomonas aeruginosa Biofilms - Duy-Khiet Ho; Chiara De Rossi; Brigitta Loretz; Xabier Murgia; Claus-Michael Lehr (MDPI AG, 2020)
The search for novel therapeutics against pulmonary infections, in particular Pseudomonas aeruginosa (PA) biofilm infections, has been intense to deal with the emergent rise of antimicrobial resistance. Despite the numerous achievements in drug discovery and delivery strategies, only a limited number of therapeutics reach the clinic. To allow a timely preclinical development, a formulation should be highly effective, safe, and most importantly facile to produce. Thus, a simple combination of known actives that enhances the therapeutic efficacy would be a preferential choice compared to advanced drug delivery systems. In this study, we propose a novel combination of an anti-inflammatory agent-itaconic acid (itaconate, IA)-and an approved antibiotic-tobramycin (Tob) or ciprofloxacin (Cipro). The combination of Tob and IA at a molar ratio of 1:5 increased the biofilm eradicating efficacy in the strain PA14 wild type (wt) by ~4-fold compared to Tob alone. In contrast, such effect was not observed for the combination of IA with Cipro. Subsequent studies on the influence of IA on bacterial growth, pyocyanin production, and Tob biofilm penetration indicated that complexation with IA enhanced the transport of Tob through the biofilm. We recommend the simple and effective combination of Tob:IA for further testing in advanced preclinical models of PA biofilm infections.